Investigation of Bioactive Compounds Extracted from Verbena officinalis and Their Biological Effects in the Extraction by Four Butanol/Ethanol Solvent Combinations - Dejan Stojković; Nikoleta Đorđevski; Mladen Rajaković; Biljana Filipović; Jelena Božunović; Stefani Bolevich; Gokhan Zengin; Sergey Bolevich; Uroš Gašić; Marina Soković (Pharmaceuticals)
Background/Objectives: Verbena officinalis L. (common vervain) is a medicinal plant traditionally used and investigated in phytotherapy for its neuroprotective, antioxidant, and anti-inflammatory properties. This study aims to investigate the phytochemical diversity and biological activity of V. officinalis extracts prepared with different ratios of butanol and ethanol. Methods: Aerial parts of V. officinalis were extracted using four solvent systems: 100% butanol (B1), 75:25 (BE7.5), 50:50 (BE5), and 25:75 (BE2.5) butanol:ethanol mixtures. Metabolite profiling was conducted using liquid chromatography–high-resolution tandem mass spectrometry (LC-HRMS/MS). Antioxidant activities were evaluated through six assays: 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), cupric ion-reducing antioxidant capacity (CUPRAC), ferric-reducing antioxidant power (FRAP), metal-chelating ability (MCA), and the phosphomolybdenum assay (PMA). Enzyme inhibition assays targeted acetylcholinesterase (AChE), butyrylcholinesterase (BChE), tyrosinase, and α-amylase. Antibacterial activity against Pseudomonas aeruginosa was tested via microdilution, while dominant phytochemicals were evaluated for binding affinity through molecular docking. Results: Seventy-five compounds, including phenolic acids, flavonoids, iridoids, phenylethanoids, and xanthones, were identified. BE5 extract exhibited the highest total phenolic content and strongest antioxidant capacity, while BE2.5 demonstrated the greatest antibacterial and metal-chelating effects. All extracts showed comparable AChE inhibition, with BE5 achieving the strongest tyrosinase and α-amylase inhibition. Docking studies confirmed high binding affinities of luteolin glucuronides to human and bacterial target enzymes. Conclusions: Solvent composition markedly influenced the chemical and biological profiles of V. officinalis extracts. BE5 and BE2.5 emerged as promising systems for obtaining bioactive fractions with therapeutic potential.